PHILOSOPHICAL IDEAS OF ABDUL QADIR BEDIL ON IMPROVING HUMAN VALU (Scientific journal of the Fergana State University, 2024)
In this article, it is stated that human value and rights embody the concepts of universality, national state, and law, and that the purpose of learning philosophy is to understand the universe, to achieve ideological and spiritual perfection, and to study the laws of rational living. Bedil's anthropological teaching is humanistic in nature and direction. The human soul is not a complex being, it has been analyzed that it encompasses all things due to its subtlety.